Fertility Preservation in Female Patients with Cancer Part II: Royan Institute Clinical Practice Guideline for Girls and Women with Cancer; A Review Study - Azar Yahyaei; Esmat Mashhadi Meighani; Firouzeh Ghaffari (International Journal of Fertility and Sterility)
The fertility preservation (FP) is a paramount concern for oncology patients and should be regarded as an essentialcomponent of their overall cancer management strategy. The magnitude of this issue has been recognized in FPguidelines. The formulation and execution of harmonized guidelines and policies concerning the provision of FPservices, inclusive of therapeutic strategies and standardization of procedures, are crucial to surmount disagreementsregarding the delivery of these therapeutic services and avert delays in cancer treatment. The matter of FP andthe methodology for managing the treatment and follow-up of cancer patients should be documented as a componentof their management guideline, thereby providing patients with clear recommendations on fertility preservation.In this manuscript, we provide a succinct overview of existing international guidelines history and referencecomprehensive networks of FP services for oncology patients. Furthermore, we present the Royan Institute’sguideline specifically designed for preserving the fertility of female oncology patients.